Focusing of high intensity ultrasound through the rib cage using a therapeutic random phased array - Bobkova, Svetlana (2010)
A method for focusing high intensity ultrasound through a rib cage that aims to minimize heating of the ribs whilst maintaining high intensities at the focus (or foci) is proposed and tested theoretically and experimentally. Two approaches, one based on geometric acoustics and the other accounting for diffraction effects associated with propagation through the rib cage, are investigated theoretically for idealized source conditions. It is shown that for an idealized radiator the diffraction approach provides a 23% gain in peak intensity and results in significantly less power losses on the ribs (1% versus 7.5% of the irradiated power) compared with the geometric one. A 2D 1-MHz phased array with 254 randomly distributed elements, tissue mimicking phantoms, and samples of porcine rib cages are used in experiments; the geometric approach is used to configure how the array is driven. Intensity distributions are measured in the plane of the ribs and in the focal plane using an infra-red camera. Theoretical and experimental results show that it is possible to provide adequate focusing through the ribs without overheating them for a single focus and several foci, including steering at ± 10–15 mm off and ± 20 mm along the array axis. Focus splitting due to the periodic spatial structure of ribs is demonstrated both in simulations and experiments; the parameters of splitting are quantified. The ability to produce thermal lesions with a split focal pattern in ex vivo porcine tissue placed beyond the rib phantom is also demonstrated. The results suggest that the method is potentially useful for clinical applications of HIFU for which the rib cage lies between the transducer(s) and the targeted tissue.